Resolution of oblique-plane images in sectioning microscopy. - Smith, C; Botcherby, E; Wilson, T (2011)
Live biological specimens exhibit time-varying behavior on the microscale in all three dimensions. Although scanning confocal and two-photon microscopes are able to record three-dimensional image stacks through these specimens, they do so at relatively low speeds which limits the time resolution of the biological processes that can be observed. One way to improve the data acquisition rate is to image only the regions of a specimen that are of interest and so researchers have recently begun to acquire two-dimensional images of inclined planes or surfaces extending significantly into the z-direction. As the resolution is not uniform in x, y and z, the images possess non-isotropic resolution. We explore this theoretically and show that images of an oblique plane may contain spectral content that could not have been generated by specimen features lying wholly within the plane but must instead arise from a spatial variation in another direction. In some cases we find that the image contains frequencies three times higher than the resolution limit for in-plane features. We confirm this finding through numerical simulations and experiments on a novel, oblique-plane imaging system and suggest that care be taken in the interpretation of such images.